Tratamento de águas de uma lavanderia industrial por flotação-filtração - Rampelotto, Geraldo (2020)
The industrial laundry sector has a high water consumption, consequently producing an abundant volume of effluent, a topic of global interest, especially due to the scarcity of water, demonstrating the importance of treating the effluents used. Laundry effluents, when properly treated, can be used for non-potable consumption in industry, such as flushing toilets, washing floors, irrigating gardens, water mirrors and fountains or in the industrial process itself through recycling, provided that do not pose risks to the health of users and have a quality standard for the proper purpose, since the environmental legislation, with each modification, becomes increasingly restrictive with regard to the quality of the water that is discarded by the companies. When discharged into water bodies, effluents can cause damage to aquatic biota, including the death of fish from intoxication, for this reason, work on ecotoxicology must be carried out. This work aimed evaluate and characterize the treatment system of a small industrial laundry, which processes around 3000 kg of clothes monthly, in real scale, aiming reuse for non-potable purposes, evaluating acute toxicity and the presence of Legionella spp. in the effluent of this laundry. The evaluation of the results of the effluent treatment allowed the discussion of the level of removal of the parameters of the proposed treatment, comparing, entry and exit of the post-treated effluent, thus validating the efficiency of the system and indicating the potential of this treatment aiming at reuse/recycling. First, a bibliographic review was carried out, using the Capes periodical portal from April 2016 to September 2019, which was based on research on water scarcity, deepening the study in the field of laundries, treatment systems and solutions, aiming to purify its liquid residues, overcome the scarcity of water and its reuse, minimizing its capture; afterwards, for the characterization and evaluation of the laundry effluents, an investigation strategy was used, involving data collection and parameter analysis, carried out from May 2015 to October 2019 (four years and four months), quantifying the production of the effluent, analysis of parameters such as temperature, pH, COD, suspended solids, mineral oils and greases and surfactants, evaluating the treatment of liquid laundry effluents, which uses the physicochemical process of dissolved air flotation (FAD) and combined with sand filters and activated carbon for polishing. Regarding toxicity research, the effluent was evaluated after treatment, using fish, Cyprinus carpio (carp) as bioindicators, with 100%, 75%, 50% and 25% raw effluent, using water from the adaptation medium for dilutions, where toxicity was assessed at 24, 48 and 72 hours of exposure. The research of Legionella spp. occurred in the raw and treated effluent in samples collected between October and November 2019. The analyze were performed in an external laboratory and followed the analytical methodology of the Standard Methods for the Examination of Water and Wastewater. In the literature review, the search resulted in 98 articles, of which 66 were selected, for addressing the proposed theme, where it was observed the existence of wastewater treatment systems with different complexities that are under study and implemented in the world, being difficult point out the best wastewater treatment system for laundromats, as each has its advantages and disadvantages. Regarding the parameters evaluated for characterization and evaluation of the laundry effluents under study, it was found that there is a wide range in the influential values for the suspended solid parameters (17.9 mg/L - 87.5 mg/L), surfactants (0.2 mg/L - 87.5 mg/L), oils and greases (5mg/L - 87.5mg/L) and COD (192.2 mg/L - 1300 mg / L), in which it was found that there is efficiency after treatment for suspended solids, surfactants, oils and greases and COD, respectively, of 54.7%; 2.4%; 43.3% and 48.5%. Regard to toxicity, it was not possible to calculate the lethal concentration (LC50) depending on the effluent that falls under the classification of slightly toxic and low mortality rate. Also, Legionella spp. did not occur. The use of Cyprinus carpio as a bioindicator was shown to have low toxicity, and the presence of Legionella spp. did not occur, and the use of effluent for reuse in relation to this microorganism can be considered safe.